CA19-9 in potentially resectable pancreatic cancer: perspective to adjust surgical and perioperative therapy - Hartwig, Werner; Strobel, Oliver; Hinz, Ulf; Fritz, Stefan; Hackert, Thilo; Roth, Maria Constanze; Büchler, Markus W.; Werner, Jens (Annals of surgical oncology, 2013)
Purpose. In pancreatic cancer, genetic markers to aid clinical decision making are still lacking. The present study was designed to determine the prognostic role of perioperative serum tumor marker carbohydrate antigen 19-9 (CA19-9) in pancreatic adenocarcinoma, with a focus on implications for pre- and postoperative therapeutic consequences. Methods. Of a total of 1,626 consecutive patients who underwent surgery for primary pancreatic adenocarcinoma, data from 1,543 patients with preoperative serum levels of CA19-9 were evaluated for tumor stage, resectability, and prognosis. Preoperative to postoperative CA19-9 changes were analyzed for long-term survival. A control cohort of 706 patients with chronic pancreatitis was used to assess the predictability of malignancy by CA19-9 and the effects of hyperbilirubinemia on CA19-9 levels. Results. The more that preoperative CA19-9 increased, the lower were tumor resectability and survival rates. Resectability and 5-year survival varied from 80 to 38 % and from 27 to 0 % for CA19-9 \37 versus C4,000 U/ml, respectively. The R0 resection rate was as low as 15 % in all patients with CA19-9 levels C1,000 U/ml. CA19-9 increased with the stage of the disease and was highest in AJCC stage IV. Patients with an early postoperative CA199 increase had a dismal prognosis. Hyperbilirubinemia did not markedly affect CA19-9 levels (correlation coefﬁcient B0.135). Conclusions. In patients with pancreatic adenocarcinoma, CA19-9 predicts resectability, stage of disease, as well as survival. Highly elevated preoperative or increasing postoperative CA19-9 levels are associated with low